Leadership and Meaningful Work in the Public Sector - Tummers, Lars G.; Knies, Eva (Public administration review, 2013)
There have been many important studies on leadership in the public administration discipline; however, scholarly inquiry still lags behind related disciplines such as psychology and business administration. This article helps fill that gap by analyzing the role that public leaders play in making work more meaningful for their employees, which, in turn, has a positive influence on employee job outcomes. Specifically, the authors analyze the mediating role of work meaningfulness in the relationships between leader-member exchange and organizational commitment, work effort, and work-to-family enrichment. Samples from education, health care, and local government are used. Results show that leadership strongly influences work meaningfulness, which, in turn, influences job outcomes. In addition, the impact and extent of leadership and work meaningfulness are higher in health care and education than in local government. The results emphasize the importance of leadership and meaningful work in the public sector.